1994
DOI: 10.1101/gad.8.12.1423
|View full text |Cite
|
Sign up to set email alerts
|

The POP1 gene encodes a protein component common to the RNase MRP and RNase P ribonucleoproteins.

Abstract: Two forms of the yeast 5.8S rRNA are generated from a large precursor by distinct processing pathways. Cleavage at site A3 is required for synthesis of the major, short form, designated 5.8S(S), but not for synthesis of the long form, 5.8S(L). To identify components required for A3 cleavage, a bank of temperature-sensitive lethal mutants was screened for those with a reduced ratio of 5.8S(S):5.8S(L). The pop1-1 mutation (for processing of precursor RNAs) shows this phenotype and also inhibits A3 cleavage. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
215
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(230 citation statements)
references
References 51 publications
12
215
2
1
Order By: Relevance
“…The 27SA' pre-rRNA cannot be detected by Northern hybridization, but primer extension through site A3, the 5' end of 27SAr, shows that its accumulation is unaffected in the GAL::diml strain (data not shown). The levels of the 5.8s rRNA and its 7s precursor are also unaffected in the GAL::diml strain, and no alteration was detected in the relative use of the alternative processing pathways that lead to the formation of the long and short forms of 5.8s rRNA , Lygerou et al 1994) (data not shown).…”
Section: Effects Of Dimzp Depletion On Pre-rrna Processingmentioning
confidence: 96%
See 1 more Smart Citation
“…The 27SA' pre-rRNA cannot be detected by Northern hybridization, but primer extension through site A3, the 5' end of 27SAr, shows that its accumulation is unaffected in the GAL::diml strain (data not shown). The levels of the 5.8s rRNA and its 7s precursor are also unaffected in the GAL::diml strain, and no alteration was detected in the relative use of the alternative processing pathways that lead to the formation of the long and short forms of 5.8s rRNA , Lygerou et al 1994) (data not shown).…”
Section: Effects Of Dimzp Depletion On Pre-rrna Processingmentioning
confidence: 96%
“…2, ITSlA3' lanes), demonstrating that the 32s pre-rRNA, or larger precursors, is methylated. Similarly, mutations in RRP2 (NMEI] or POPI, which encode the RNA and protein components of RNase MRP, respectively, also delay synthesis of 20s pre-rRNA (Lygerou et al 1994) and lead to methylation of the 32s pre-rRNA (data not shown). Because the processing of 32s to 20s pre-rRNA is nucleolar, methylation can occur in the nucleolus.…”
Section: Subcellular Localization Of the Dimethylation Eventmentioning
confidence: 99%
“…RNase MRP is implicated in the cleavage of pre-rRNA at site A3 within ITS1 (Lygerou et al, 1994). RNase P participates in cleavages in the 5Ј-ETS, ITS1, and ITS2 of the primary 35S pre-rRNA transcript in yeast (Chamberlain et al, 1996;Stolc and Altman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, a previous report identifying multiprotein subunit association with RNase MRP (mitochondrial RNA processing) activity also supports this notion. RNase MRP enzyme is a ribonucleoprotein that is closely related to RNase P: they contain RNA components having secondary structure similarities 1401, share a common epitope 1411 and a protein component [42], and have nuclear-encoded protein subunits. Pulse-chase labeling of HeLa cells and purification of the RNase mitochondrial RNA processing enzyme revealed that about 10 polypeptides, with molecular masses in the range 10-100 kDa, were copurified with the enzyme activity 1431.…”
Section: Discussionmentioning
confidence: 99%